Effect of in vivo post-translational modifications of the HMGB1 protein upon binding to platinated DNA: a molecular simulation study. Issue 22 (8th November 2018) - (Lv), Wenping Lyu; Arnesano, Fabio; Carloni, Paolo; Natile, Giovanni; Rossetti, Giulia
Abstract: Cisplatin is one of the most widely used anticancer drugs. Its efficiency is unfortunately severely hampered by resistance. The High Mobility Group Box (HMGB) proteins may sensitize tumor cells to cisplatin by specifically binding to platinated DNA (PtDNA) lesions. In vivo, the HMGB/PtDNA binding is regulated by multisite post-translational modifications (PTMs). The impact of PTMs on the HMGB/PtDNA complex at atomistic level is here investigated by enhanced sampling molecular simulations. The PTMs turn out to affect the structure of the complex, the mobility of several regions (including the platinated site), and the nature of the protein/PtDNA non-covalent interactions. Overall, the multisite PTMs increase significantly the apparent synchrony of all the contacts between the protein and PtDNA. Consequently, the hydrophobic anchoring of the side chain of F37 between the two cross-linked guanines at the platinated site—a key element of the complexes formation - is more stable than in the complex without PTM. These differences can account for the experimentally measured greater affinity for PtDNA of the protein isoforms with PTMs. The collective behavior of multisite PTMs, as revealed here by the synchrony of contacts, may have a general significance for the modulation of intermolecular recognitions occurring in vivo .